Cartographic Competence in Higher Geographical Education Research: A Review of the Field - K. D. Kaimuldinova; A. N. Beikitova; G. M. Sabdenalieva; G. O. Zhandosova (Moscow Polytechnic University, 2024)
The formation of cartographic competence is an urgent task of higher geographical education.   The purpose of the study is to review current trends, summarize the results of research available in the literature, characterize the subject field of cartographic competence research and identify gaps in scientific knowledge regarding cartographic competence.   To achieve it, the following tasks were solved: to reveal the essence of the concept of "cartographic competence" and the concepts of "cartographic literacy" close to it, "skills of reading geographical maps", "spatial thinking"; based on the analysis of the literature, identify the most researched issues and gaps in scientific knowledge in the field of cartographic competence; identify promising areas for further research. A review of research on the formation of cartographic competence was conducted on the basis of analysis and meta-analysis methods according to the PRISMA 2020 criteria by sampling literature by keywords.   Research results: a review of research on the definitions of the concept of "cartographic competence" and related concepts was carried out; the most researched problems of cartographic competence and empirical data obtained within the framework of this topic were identified; gaps existing in scientific knowledge were identified; the most promising areas of further research in the field of cartographic competence were identified.